2010
DOI: 10.1002/bsl.946
|View full text |Cite
|
Sign up to set email alerts
|

Use of third party information in child custody evaluations

Abstract: This article reviews the use of third party information and its potential to increase the accuracy and usefulness of child custody evaluations. Legal and admissibility issues are reviewed, along with the types of third party information commonly utilized. Factors impacting such data sources are discussed, as well as the importance of determining the degree to which independent sources point to the same conclusion. Suggestions are provided for selecting, contacting, and interviewing collateral sources, and ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They found that 89% of the mental health professionals evaluating were licensed psychologists, of which 85.5% held doctoral degrees. Bow (2010) surveyed 117 psychologists, of which 97% held doctoral degrees. Bow and Boxer (2003) surveyed 155 mental health professionals and found that 68% were doctoral-level psychologists.…”
Section: Resultsmentioning
confidence: 99%
“…They found that 89% of the mental health professionals evaluating were licensed psychologists, of which 85.5% held doctoral degrees. Bow (2010) surveyed 117 psychologists, of which 97% held doctoral degrees. Bow and Boxer (2003) surveyed 155 mental health professionals and found that 68% were doctoral-level psychologists.…”
Section: Resultsmentioning
confidence: 99%
“…While now somewhat dated, research by Kirkland et al (2005) indicated that some experienced evaluators had moved towards written forms and questionnaires “designed to assess third party opinions in a more standardized fashion.” (p. 102). While records requests and structured forms have some drawbacks due to lack of immediate elaboration (Bow, 2010), they may serve as a reasonable “first pass” at data review to determine which current professionals should be contacted for additional follow‐up interviews or other requests for elaboration. In a setting where time and resources are limited, playing “phone tag” or otherwise investing in scheduling long interviews with professionals who may provide information of only limited relevance wastes effort chasing low‐quality information.…”
Section: Methodological Considerationsmentioning
confidence: 99%